Die Neumitgliederwerbung von SPD und CDU im Vergleich Strategielose Mitgliederpartei oder überfordertes Ehrenamt? - Jakobs, Simon (Parteien in Theorie und Empirie, 2021)
Is the loss of members of German popular parties an unstoppable scenario of decline or a reversible phenomenon? The first systematic research shows in a comparative analysis of the strategies of the German parties CDU and SPD in recruiting new party members that it is worthwhile to enter a completely new field of investigation. The study reveals that the loss of members can be stopped at the cost of further professionalization of party members.